Anaesthetics as cardioprotectants: translatability and mechanism - Kikuchi, C (Br J Pharmacol, 2015)
The pharmacological conditioning of the heart with anaesthetics, such as volatile anaesthetics or opioids, is a phenomenon whereby a transient exposure to an anaesthetic agent protects the heart from the harmful consequences of myocardial ischaemia and reperfusion injury. The cellular and molecular mechanisms of anaesthetic conditioning appear largely to mimic those of ischaemic pre- and post-conditioning. Progress has been made on the understanding of the underlying mechanisms although the order of events and the specific targets of anaesthetics that trigger protection are not always clear. In the laboratory, the protection afforded by certain anaesthetics against cardiac ischaemia and reperfusion injury is powerful and reproducible but this has not necessarily translated into similarly robust clinical benefits. Indeed, clinical studies and meta-analyses delivered variable results when comparing in the laboratory setting protective and non-protective anaesthetics. Reasons for this include underlying conditions such as age, obesity and diabetes. Animal models for disease or ageing, human cardiomyocytes derived from stem cells of patients and further clinical studies are employed to better understand the underlying causes that prevent a more robust protection in patients.